2014
DOI: 10.1186/1745-6215-15-235
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to reduce excessive alcohol consumption and improve comorbidity outcomes in hypertensive or depressed primary care patients: two parallel cluster randomized feasibility trials

Abstract: BackgroundMany primary care patients with raised blood pressure or depression drink potentially hazardous levels of alcohol. Brief interventions (BI) to reduce alcohol consumption may improve comorbid conditions and reduce the risk of future alcohol problems. However, research has not established their effectiveness in this patient population. This study aimed to establish the feasibility of definitive trials of BI to reduce excessive drinking in primary care patients with hypertension or mild to moderate depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…That lower cut-offs may be inappropriate is also illustrated by the lower effect sizes found in an updated Cochrane review, where the average baseline consumption at enrolment had dropped to 183g/week 60 . It has also been suggested that PHC providers might be more engaged in screening and giving brief advice, if screening were targeted to patients with comorbid conditions, such as depression or hypertension 30 , 61 , 62 . However, to date, there is insufficient evidence for an appropriate package that deals with comorbidity to scale-up 63 .…”
Section: Introductionmentioning
confidence: 99%
“…That lower cut-offs may be inappropriate is also illustrated by the lower effect sizes found in an updated Cochrane review, where the average baseline consumption at enrolment had dropped to 183g/week 60 . It has also been suggested that PHC providers might be more engaged in screening and giving brief advice, if screening were targeted to patients with comorbid conditions, such as depression or hypertension 30 , 61 , 62 . However, to date, there is insufficient evidence for an appropriate package that deals with comorbidity to scale-up 63 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Wilson et al studied the AUDIT scores in Hypertensive patients. 11 Alcohol consumption in any form is Increasing in rural as well as in tribal pockets of the country, also the lack of awareness about the hazardous effects of its consumption makes the situation grim & alarming therefore we opted for this study to explore the magnitude of the problem not only in rural non-tribal but also in tribal people of this backward tribal district of Madhya Pradesh-Mandla.…”
Section: Introductionmentioning
confidence: 99%
“…We set the same cut-offs for men and women, based on epidemiological evidence [85], and to minimize unintended consequences of using different cut offs for men and women [86]. We recognize the importance of comorbid depression [87,88] by building in identification, management, and referral mechanisms [89,90];…”
Section: Discussionmentioning
confidence: 99%